DETERMINATION OF COORDINATES OF COG'S SIDES OF THE GEARS WITH ELLIPTIC PROFILE - A.A. RYZHKIN; A.A. ANDROSOV; G.P. GREBENJUK; M.V. SAVENKOV; V.V. VYALAYA (Advanced Engineering Research)
Results of theoretical definition of coordinates of a cog side having in normal cross-section the elliptic profile are presented. Equations connecting angular and linear dimensions of cogs in face and normal cross-sections are obtained. The offered technique is usable for a determination of coordinates of the profile circumscribed by any plane curve of the second order.